The Relationship Between Numerical Ability and Mathematical Problem-Solving Ability on the Topic of Three-Variable Linear Equation Systems - Ainiyyah, Uray Tantri; Septianawati, Desty; Sulisti, Hidayu (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The objective of this study is to describe: the numerical ability in the topic of three-variable linear equation systems among Grade X students of SMA Negeri 10 Pontianak; the mathematical problem-solving ability in the same topic among the same group of students; and the relationship between numerical ability and mathematical problem-solving ability in that topic. This study employs a correlational research design with a quantitative approach. The sampling technique used was proportional sampling, selecting 30% of the total population, resulting in a sample of 108 students. The data collection techniques used were tests and documentation. The data were analyzed using descriptive statistics and the Pearson correlation test. The results of this study indicate a significant positive relationship between numerical ability and mathematical problem-solving ability. The strength of the relationship between the two abilities among Grade X students of SMA Negeri 10 Pontianak is 24.0%.